Parallel labeled-line organization of sympathetic outflow for selective organ regulation in mice - Yukiko Harima; Masafumi Tsurutani; Serika Yamada; Shuntaro Uchida; Kengo Inada; Mitsue Hagihara; Satsuki Irie; Mayo Shigeta; Takaya Abe; Yukiko U. Inoue; Takayoshi Inoue; Kazunari Miyamichi (Nature Communications)
Abstract The sympathetic nervous system is crucial for responding to environmental changes. This regulation is coordinated by the spinal sympathetic preganglionic neurons (SPNs), innervating both postganglionic neurons and the adrenal gland. Despite decades of research supporting the concept of selective control within this system, the neural circuit organization responsible for the output specificity remains poorly understood. Here, by combining recent single-cell transcriptome data with viral-genetic toolkits in mice, we identify two subtypes of SPNs in the lower thoracic spinal cord, defined at the molecular level, exhibiting nonoverlapping patterns of innervation: one specifically projecting to the celiac/superior mesenteric ganglia, and the other targeting the adrenal grand. Chemogenetic manipulations on these distinct SPN subtypes revealed selective impacts on the motility of the gastrointestinal tracts or glucose metabolism mediated by the adrenal gland, respectively. This molecularly delineated parallel labeled-line organization in sympathetic outflows presents a potential avenue for selectively manipulating organ functions.